MORFOSINTAKSIS VERBA BAHASA TONSEA - Lagarens, Yollanda (Kajian Linguistik, 2018)
This research deals with the morphosyntax of Tonsea Language verb. The analysis of morphosyntax verb in Tonsea Language is based on the theory developed by Nida (1970) who described that the study of morphosyntax is a structural analysis in which one cannot treat the morphology without at the same time analyzing the syntax. The contact point of these two areas lies in the analysis of inflectional affixation of verbs in sentence structure. It is a qualitative research applying structural linguistic method. The result indicates that the inflectional affixation of verbs in Tonsea Language shows the category of tense, aspect, mood, and voice.Keywords: morphosyntax, inflectional affixes